2023
DOI: 10.3390/ijms24043779
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Profiling of Skeletal Muscle in Two Pig Breeds Reveals CircIGF1R Regulates Myoblast Differentiation via miR-16

Abstract: Muscle development is closely related to meat quality and production. CircRNAs, with a closed-ring structure, have been identified as a key regulator of muscle development. However, the roles and mechanisms of circRNAs in myogenesis are largely unknown. Hence, in order to unravel the functions of circRNAs in myogenesis, the present study explored circRNA profiling in skeletal muscle between Mashen and Large White pigs. The results showed that a total of 362 circRNAs, which included circIGF1R, were differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Sun et al reported the ceRNA network of miR-21-3p/CDK16 mediated by circCSDE1, which regulates pig muscle development ( Sun et al, 2022 ). Li et al constructed the regulatory network of porcine skeletal muscle differentiation with circIGF1R/miR-16/mRNA through sequencing and bioinformatics analysis ( Li et al, 2023 ). It is reported that circRNA can participate in the regulation of muscle development by affecting the expression of marker genes in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al reported the ceRNA network of miR-21-3p/CDK16 mediated by circCSDE1, which regulates pig muscle development ( Sun et al, 2022 ). Li et al constructed the regulatory network of porcine skeletal muscle differentiation with circIGF1R/miR-16/mRNA through sequencing and bioinformatics analysis ( Li et al, 2023 ). It is reported that circRNA can participate in the regulation of muscle development by affecting the expression of marker genes in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…By sequencing the longissimus dorsi muscle of Jinfen pig, Sun et al discovered that circCSDE1 regulated the expression of CDK16 by binding to miR-21-3p, and verified on C2C12 that circCSDE1 promoted myoblast proliferation and inhibited myoblast differentiation ( Sun et al, 2022 ). Li et al examined that circIGF1R promoted the differentiation of porcine myoblasts by adsorbing miR-16 regulatory gene expression ( Li et al, 2023 ). Wang et al reported that Gm10561 can upregulate E2F3 and MEF2C via targeted binding to miR-432 and promote the proliferation and differentiation of muscle cells in pigs and mice ( Wang et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CDR1as functions as an efficient miRNA sponge, binding miR-7 and allowing mRNAs to escape degradation following miRNA binding [ 33 ]. Besides, circRNAs serve as miRNAs “sponges” to control pig muscle development [ 13 , 15 , 34 , 35 ]. However, its role in ceRNA regulation during spleen development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In goats, circUSP13 adsorbs miR-29c to target and regulate IGF1 to promote differentiation and inhibit apoptosis in goat myoblasts [122]; circUBE3A acts as a miR-28-5p sponge to promote myogenic cell proliferation and differentiation [123]. In pigs, circIGF1R targets miR-16 and promotes myoblast differentiation [124]. These processes suggest that circRNAs can play an important function in regulating muscle development by acting as molecular sponges for miRNAs to inhibit miRNA activity.…”
Section: Lncrnas Regulate Skeletal Muscle Through Cis or Trans Gene E...mentioning
confidence: 99%